STUDY OF IMPROVING THE IRRIGATION NETWORK SYSTEM FOR THE SALURAN INDUK MADIUN (SIM) IN MAGETAN REGENCY - Nusantara, Danayanti Azmi Dewi; Fawati, Isroul Akbar (Fakultas Teknik Universitas Tanjungpura, 2023)
The Saluran Induk Madiun, abbreviated as SIM, is the primary waterway that irrigates the SIM Irrigation Area. Jati Dam, located in Gondangan Village, Gorang-Gareng District, Magetan Regency, is the primary source of the SIM Irrigation Area. This SIM Irrigation Area gets its main supply from Jati Dam; Jati Dam is the upstream or the beginning of the flow in the SIM Irrigation Area. In conditions before rehabilitation, the Jati Dam had a discharge of 4000 l/s to irrigate the entire SIM Irrigation Area. Especially for the SIM Irrigation Area in Magetan Regency, obtaining water supply from the Jati Dam at 17% of 350,746 l/s, the discharge value can only meet the paddy cropping pattern of 30%. Looking at these problems, the Government of Indonesia is seeking rehabilitation work to increase agricultural barns production. Therefore, it is necessary to research the improvement of irrigation network systems to determine the ratio of water availability before and after rehabilitation, water demand, and the value of increasing agricultural profits. This research uses the F.J. Mock to assess the availability of water discharge FAO Modified Penman Method and the amount of evapotranspiration used to analyze water demand for each cropping pattern. A comparison of the value of the availability and demand for water is presented in the form of a water balance.From the results of the analysis that has been carried out, it is concluded that the highest water availability in the SIM Irrigation Area in Magetan Regency before rehabilitation was 1.37 m3/sec, and the lowest was 0.74 m3/sec. In conditions after rehabilitation, the highest was 5.75 m3/sec, and the lowest was 4.64 m3/sec. It is known that the supply from the Jati Dam, in conditions before rehabilitation, was 17%, and in conditions after rehabilitation, it increased to 28%. The highest irrigation water requirement is the cropping pattern that uses 100% paddy of 3.01 m3/sec. Seeing the value of water availability compared to the still significant water demand, the Jati Dam intake can be reduced from 28% to 20% so that the remaining water can be distributed to the following secondary waterways. Water availability at a percentage of 28% is 5.75 m3/sec; at 20%, it becomes 3.49 m3/sec. This debit can fulfill the highest water demand of 3.01 m3/sec. In conditions before rehabilitation, the availability of water was only able to meet the planting pattern of Paddy (30%) - Paddy (25%) - Secondary crops (100%) with a profit of Rp.26,161,069,519.00. Whereas in conditions after rehabilitation, the availability of water can fulfill the planting pattern of Paddy (100%) - Paddy (100%) - Paddy (100%) with a profit reach up to Rp.115,325,883,740.00.